Cutaneous manifestations of graft‐versus‐host disease: role of the dermatologist. (23rd September 2016) - Kavand, Sima; Lehman, Julia S.; Hashmi, Shahrukh; Gibson, Lawrence E.; el‐Azhary, Rokea A.
Summary: Graft‐versus‐host disease (GVHD) is the major complication of hematopoietic stem cell transplantation and is associated with high mortality in severe cases. The skin is one of the major organs affected in both acute and chronic GVHD. This review aims to elucidate the basic characteristics of GVHD, and the role and contribution of dermatologists in the care of patients with this condition.